2017
DOI: 10.1021/acs.jafc.6b05517
|View full text |Cite
|
Sign up to set email alerts
|

Emulsifying Properties of Oxidatively Stressed Myofibrillar Protein Emulsion Gels Prepared with (−)-Epigallocatechin-3-gallate and NaCl

Abstract: The dose-dependent effects of (-)-epigallocatechin-3-gallate (EGCG; 0, 100, or 1000 ppm) on the textural properties and stability of a myofibrillar protein (MP) emulsion gel were investigated. Addition of EGCG significantly inhibited formation of carbonyl but promoted the loss of both thiol and free amine groups. Addition of EGCG, particularly at 1000 ppm, initiated irreversible protein modifications, as evidenced by surface hydrophobicity changes, patterns in sodium dodecyl sulfate-polyacrylamide gel electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 39 publications
3
69
1
Order By: Relevance
“…However, Feng et al. () showed that EGCG at a high dose (1000 mg/g) led to irreversibly protein modification, probably due to interactions between the quinone of EGCG and the sulfhydryl groups and free amines of the proteins. This resulted in high cooking loss and a weakened emulsion structure.…”
Section: Antioxidant Activity Of Egcgmentioning
confidence: 99%
“…However, Feng et al. () showed that EGCG at a high dose (1000 mg/g) led to irreversibly protein modification, probably due to interactions between the quinone of EGCG and the sulfhydryl groups and free amines of the proteins. This resulted in high cooking loss and a weakened emulsion structure.…”
Section: Antioxidant Activity Of Egcgmentioning
confidence: 99%
“…After treatment with β‐ME (Figure 5B), polymers at the top of the stacking gel decreased and most bands of the MHC, tropomyosin, and actin bands were recovered. This finding indicated that the polymers were primarily formed by disulfide bonds (Feng et al., 2017). In fact, polymers can be formed by intra‐ and intermolecular cross‐links of proteins, and by the cross‐links of lipid oxidation byproducts with proteins (e.g., MDA react with proteins to form bis‐Schiff base diimine) (Requena et al., 1996).…”
Section: Resultsmentioning
confidence: 97%
“…This study was in accordance with those previous reports in which phenolic compounds inhibited protein carbonyl content, such as quercetin [27] ,rosmarinic acid [28] and EGCG. [29,30] Total and free sulfydryl groups MP is rich in sulfydryl groups, which are susceptible to attack by reactive oxygen species and can then convert to intra-and intermolecular disulfide bond linkages. [10] As shown in Table 1, the total sulfydryl group content of control MP was 109.63 nmol/mg protein.…”
Section: Carbonyl Contentmentioning
confidence: 99%
“…This study was consistent with other previous reports which indicate that phenolic compounds inhibit the surface hydrophobicity. [29] It is also shown that phenolic compounds can protect protein side-chain groups.…”
Section: Carbonyl Contentmentioning
confidence: 99%